DAMPAK KOMUNIKASI INTERPERSONAL DAN DUKUNGAN SOSIAL TERHADAP KEPUASAN PERNIKAHAN PADA ANGGOTA KEPOLISIAN RESOR PEKALONGAN - Pamela Rosana Latifah Hidayah; Dyah Astorini Wulandari; Rr. Setyawati; Uswatun Hasanah (CV. Denasya Smart Publisher, 2025)
Marital satisfaction refers to the extent to which an individual feels emotionally comfortable, harmonious, and happy in their marital relationship. This satisfaction is influenced by how couples communicate and the degree to which social support is present in their lives. This study aims to examine the influence of interpersonal communication and social support on marital satisfaction among members of the Pekalongan Police Resort. The research uses a quantitative approach with purposive sampling techniques. A total of 201 members of the Pekalongan Police Resort participated in the study. The instruments used include the Interpersonal Communication Scale (MCI), the Social Support Scale (SSQ), and the Marital Satisfaction Scale (EMS). Data were collected using the interpersonal communication scale, social support scale, and marital satisfaction scale. Data analysis was conducted using multiple linear regression with the help of SPSS version 27.00. The analysis results showed a t-value of 6.076 for the influence of interpersonal communication on marital satisfaction, and a t-value of 4.980 for the influence of social support on marital satisfaction. The F-value of 22.675 indicates a significant influence of interpersonal communication and social support on marital satisfaction. With an R Square of 18.6%, this study suggests that interpersonal communication and social support contribute effectively to 18.6% of marital satisfaction, while the remaining percentage is influenced by other factors not examined in this research. These findings highlight the importance of interpersonal communication in creating a satisfying marriage, as well as the role of social support in helping couples cope with life’s pressures.